2020
DOI: 10.1038/s41394-020-0257-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, concern of falling and satisfaction of the sit-ski aid in sit-skiers with spinal cord injury: observational study

Abstract: Study design Observational study. Objective To describe (1) user satisfaction, (2) the Quality of Life (QoL) and (3) fear of falling in individuals with tetraplegia or paraplegia who used a mono-ski for sit-skiing. Setting Spinal units and Sport associations. Methods An observational study of people with spinal cord injury (SCI) who used a sit-ski. Participants were recruited in various SCI rehabilitation centers and sport associations. Participants completed three assessment tools: the Quebec User Evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…Particularly for wheelchair users, who have severely limited opportunities for meaningful outdoor leisure activities, it may be one of the suitable options for active spending of their leisure time in winter. These findings are consistent with the results of the Ponti study [34], where it is documented that mono-skiing correlates with high levels of satisfaction, low levels of fear of falling and increased quality of life. Taking into account other thematically related publications, it can be concluded that mono-skiing is clearly recommended for sports therapy programs for these reasons.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Particularly for wheelchair users, who have severely limited opportunities for meaningful outdoor leisure activities, it may be one of the suitable options for active spending of their leisure time in winter. These findings are consistent with the results of the Ponti study [34], where it is documented that mono-skiing correlates with high levels of satisfaction, low levels of fear of falling and increased quality of life. Taking into account other thematically related publications, it can be concluded that mono-skiing is clearly recommended for sports therapy programs for these reasons.…”
Section: Discussionsupporting
confidence: 92%
“…Kvasnička [23] states that downhill skiing on mono-ski is a young sport that has seen great development in recent years. Thanks to the technological maturity of compensatory aids, it can be practiced by individuals with severe physical or combined disability [34,25,15]. Petrofsky [33] demonstrated that mono-skiing correlates with high levels of satisfaction among mono-skiers, low levels of fear of falling and an increase in their quality of life.…”
Section: Downhill Skiing For Individuals With Disability and The Situation In The Czech Republicmentioning
confidence: 99%
“…The perceived ability of a person to perform tasks successfully and confidence in skills has been shown as an important factor of health results (Craig et al, 2013). Self-efficacy has a mediating role between stress and depression and has effects against the negative impacts of pain and fatigue (Ponti et al, 2020). User 5 had low upper body strength when she started to use a wheelchair and believed that the prototype is an excellent place to start to learn the technique of sit-skiing without wearing herself out.…”
Section: "When I Got Ill I Felt Like I Lost a Part Of Myself I Had No...mentioning
confidence: 99%
“…Some research to date has suggested that engagement with sport can both positively and negatively affect dimensions of para-athlete well-being (Puce et al, 2023). For example, regular exercise improves bone metabolism and immunology, as well as increases mobility and functional independence—contributing to positive physical well-being (Ponti et al, 2020). However, the benefits of sport participation can be overridden by commonplace issues like illness or injury, overtraining, or unhealthy nutritional practices (Brook et al, 2019).…”
mentioning
confidence: 99%